Nanodispersions Interactions, Stability, and Dynamics - Ruckenstein, Eli.; Manciu, Marian; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book collects a number of papers on nanodispersion interactions, dynamics and stability by Eli Ruckenstein and his research group at The State University of New York at Buffalo. Each paper provides insight into nanotechnology and fills the growing need for a basic understanding of nanoparticle interactions and their role in the thermodynamic or kinetic stability of nanodispersions. They should appeal to those applying nanotechnology to chemistry, biophysics, materials science, colloid science, polymer science, and chemical engineering.
Coagulation, dissociation and growth of aerosols -- Dynamics of deposition of Brownian particles or cells on surfaces -- Stability of dispersions -- Non-DLVO colloidal interactions: excluded volumes, undulation interactions, depletion forces and many-body effects -- Non-DLVO colloidal interactions: specific ion effects explained by ion-hydration forces -- Polarization Model: a unified framework for hydration and double layer interactions -- Polarization Model and ion specificity: applications -- Polymer brushes.
Keywords: Materials; Polymers; Chemical engineering; Nanotechnology; Surfaces (Physics).; Material Science; Nanotechnology; Surfaces and Interfaces, Thin Films; Polymer Sciences; Industrial Chemistry/Chemical Engineering; Biophysics and Biological Physics